Brief Information on Scleral Contact Lens - Chowdhury, Partha Haradhan; Shah, Brinda Haren; Tiwari, Nripesh (International Journal For Research In Health Sciences And Nursing, 2020)
Scleral Contact lens rests on the sclera/conjunctiva and some part of the cornea also. It is the first contact lens which is discovered. It is too expensive compared to other contact lens. Scleral contact lensis also known as Haptic contact lens. Especially Scleral contact lens are prescribed during high Keratoconus (where RGP is not stable on the cornea) and in Arthritis patients. In case of significant refractive error these lenses are advised to use.